Obeah, Orisa, and Religious Identity in Trinidad, Volume II, Orisa : Africana Nations and the Power of Black Sacred Imagination, Volume 2. - Stewart, Dianne M. (Religious Cultures of African and African Diaspora People Series, 2022)
Dianne M. Stewart analyzes the sacred poetics, religious imagination, and African heritage of Yoruba-Orisa devotees in Trinidad from the mid-nineteenth century to the present.